2016
DOI: 10.7717/peerj.2486
|View full text |Cite
|
Sign up to set email alerts
|

Validation of picogram- and femtogram-input DNA libraries for microscale metagenomics

Abstract: High-throughput sequencing libraries are typically limited by the requirement for nanograms to micrograms of input DNA. This bottleneck impedes the microscale analysis of ecosystems and the exploration of low biomass samples. Current methods for amplifying environmental DNA to bypass this bottleneck introduce considerable bias into metagenomic profiles. Here we describe and validate a simple modification of the Illumina Nextera XT DNA library preparation kit which allows creation of shotgun libraries from sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 61 publications
(77 reference statements)
5
95
1
Order By: Relevance
“…First, resuspending viruses from soils is a challenge due to their adsorption to the soil matrix (43). Second, yields of viral DNA are often very low (due to both low input biomass and potentially low extraction efficiency), requiring amplification; this leads to biases (53, 5661) or poor assembly and few viral contigs (described further in 125). Third, viral contig identification requires a reference database, yet soil viruses are underrepresented in current databases; for example, a majority (85%) of our sequence space was unknown.…”
Section: Resultsmentioning
confidence: 99%
“…First, resuspending viruses from soils is a challenge due to their adsorption to the soil matrix (43). Second, yields of viral DNA are often very low (due to both low input biomass and potentially low extraction efficiency), requiring amplification; this leads to biases (53, 5661) or poor assembly and few viral contigs (described further in 125). Third, viral contig identification requires a reference database, yet soil viruses are underrepresented in current databases; for example, a majority (85%) of our sequence space was unknown.…”
Section: Resultsmentioning
confidence: 99%
“…MDA, SISPA), the read composition of a PCR-amplified metagenome should accurately reflect the original community composition. This has been previously demonstrated [17], and could be verified here by observing the coverage of reference contigs (obtained from unamplified metagenomes) in PCR-amplified metagenomes. Overall, nearly all contigs assembled from unamplified metagenomes were detected in PCR-amplified datasets (>90% of contigs with ≥ 5x average coverage depth, Table S2), and there was a strong correlation between unamplified and PCR-amplified coverage for shared contigs (average Pearson correlation r 2 =0.77 for Nextera XT and 1S Plus library methods, Table S2, Fig.…”
Section: Insert Length Bias Of Pcr Amplification Leads To Uneven Covesupporting
confidence: 81%
“…However, strong amplification biases make these approaches unsuitable for quantitative estimations of taxa or genes relative abundance [24,25]. Alternatively, tagmentation or adaptase protocols allow subnanogram DNA inputs for adapter ligation, and then use PCR (typically ≥ 9 cycles) to amplify the ligated DNA [17,26]. In contrast to whole genome amplification, these protocols yield metagenomes (hereafter "PCR-amplified metagenomes") for which read mapping enables a quantification of taxa and/or genes, and are thus the methods of choice for low-input metagenomes.…”
Section: Introductionmentioning
confidence: 99%
“…Our data shows that an NGS-based approach has the advantage that not only single genes but a wide range of marker genes, such as the full rRNA operon as well as the full mitochondrial genome can be recovered from shallow sequencing depths. Recent studies have shown that successful library preparation can be done from as little as 1 picograms of DNA (Rinke et al 2016) and has been used on a range of microscopic eukaryotic taxa (Jäckle et al 2018, Gruber-Vodicka et al 2019, Seah et al 2019). Commercially available kits allow input amounts as low as 1 ng of DNA, and have been used for low cost library construction protocols (Therkildsen & Palumbi 2017).…”
Section: Discussionmentioning
confidence: 99%